390 Emerging safety and activity data from GEN-009–101: A phase 1/2a trial of GEN-009, a neoantigen vaccine in combination with PD-1 check-point inhibitors (CPI) in advanced solid tumors. (9th November 2020) - Gillison, Maura; Cohen, Roger; Twardowski, Przemyslaw; Sukari, Ammar; Johnson, Melissa; Lackner, Rudy; Davis, Thomas; DeCillis, Arthur; Hernandez, Richard; Price, Jessica; Mancini, Kevin; Shainheit, Mara; et al.
Abstract : Background: GEN-009 is an adjuvanted personalized cancer vaccine containing up to 20 neoantigens selected by ATLAS™, an ex vivo bioassay screening autologous T cells to identify both neoantigens as well as Inhibigens™ empirically and without in silico predictions. Inhibigen-specific T cells suppress immunity and have been shown to accelerate tumor progression in mice. Inhibigens are avoided in GEN-009. Previous data from patients treated with GEN-009 monotherapy showed 99% of selected peptides generated immune responses including ex vivo CD4 + and CD8 + fluorospot responses specific for 51% and 41% of immunized peptides respectively. Methods: GEN-009 is being evaluated in patients (pts) with advanced cancer who received standard-of-care (SOC) PD-1 inhibitor as monotherapy or in combination therapy during vaccine manufacturing; they subsequently received 5 vaccine doses over 24 weeks in combination with the PD-1 inhibitor. Patients who progressed prior to vaccination could receive alternate therapy followed by GEN-009 combined with an appropriate salvage regimen. Peripheral T cell responses were evaluated pre-and post-vaccination by dual-analyte fluorospot assays measured both directly ex vivo and after in vitro stimulation. Results: As of August 18, 2020, 15 pts received GEN-009 in combination with a PD-1 inhibitor. Their median TMB was 1.37Mut/mb (range 0.31–6.55), with a median of 24 (6–99) neoantigens and 16 (1–86) Inhibigens. The number of neoantigens in each manufactured vaccine ranged from 4–18 (median 13). GEN-009-related adverse events were limited to Grade 1 injection site reactions. Ex vivo T cell responses peaked after the third vaccination for IFNγ and some patients showed evidence of epitope spread. The initial 5 patients are evaluable for antitumor activity with at least 3 months follow up after first vaccination. Three patients experienced early tumor responses followed by stabilization on PD-1 inhibitor SOC and demonstrated a further reduction in tumor volume after GEN-009 vaccination (figure 1). One patient experienced a complete response prior to vaccination and the 5th patient had progression on SOC, but had a Partial Response to salvage and remains stable after vaccination. Conclusions: Vaccination with GEN-009 in combination with PD-1 CPI is feasible for patients with advanced solid tumors with little additive toxicity. Preliminary data demonstrate induction of robust, neoantigen-specific immune responses and a potential expansion of stimulatory targets with epitope spreading in the presence of PD-1 inhibitor. Possible additive antitumor activity in combination with PD-1 inhibitors is suggested by tumor shrinkage following GEN-009 dosing. More mature response and immunogenicity data on 10 additional patients is anticipated for November. Trial Registration: ClinicalTrials. gov NCT03633110 Ethics Approval: The study was approved by Western Institutional Review Board, approval number 1-1078861-1.